Rancang Bangun Film Pendek Animasi 3d Berjudul Level Up Menggunakan Blender Versi 3.2 - Junidar, Junidar; Sukiakhy, Kikye Martiwi; Umam, Teuku Khairul (J-SIGN (Journal of Informatics, Information System, and Artificial Intelligence), 2023)
A short 3D animation film titled Level Up tells about a robot that wants to create a work using different illustrations, namely blueprints and Blender. The purpose of making this animated 3D short film is to increase understanding of illustrations in 3D object design, where using the Blender 3.2 application the design process will be easier to do. This film has a video resolution of 1920x1080 and a frame rate specification of 30 frames per second with the .mp4 extension. Designing and creating videos using the Blender application which refers to the process of storyboarding, modeling, texturing, animation, lighting, rendering, Adobe Premiere Pro and Vlog Now for video editing. With this 3D animated short film, it is hoped that it can be a reference in making other works.